Pengembangan Kreativitas dan Rasa Percaya Diri Siswa SMP Melalui Pelatihan Tari Tradisional di Jorong Balai Baruah - Nuzul Hidayat; Adrian Adrian; Akram Maulana Yamin; Aufadhila Andris; Desriani Dwi Putri; Gema Takbir Riraya; Salma Qolbi (CV. ITTC INDONESIA, 2026)
The preservation of local culture requires educational activities that actively engage younger generations. One effort that can be implemented is traditional dance training as a medium for character development and skill enhancement among students. This community service program aimed to develop the creativity and self-confidence of junior high school students through traditional dance training in Jorong Balai Baruah, Batu Bajanjang Village, Lembang Jaya District, Solok Regency. The program employed the Participatory Learning and Action (PLA) approach, which emphasizes active participant involvement throughout all stages of the activity. The program was carried out through several stages, including initial observation, program planning, traditional dance training implementation, and evaluation. Data were collected through participatory observation, documentation, and assessments of students’ progress during the training process. The results indicated that traditional dance training successfully enhanced students’ creativity, as reflected in their ability to develop movement variations, participate actively in group practices, and express themselves through dance performances. Furthermore, students demonstrated increased self-confidence, which was evident from their willingness to perform in public, communicate within groups, and actively engage in all training activities. The program also contributed to the preservation of local culture by improving students’ understanding of the cultural values embedded in Minangkabau traditional dances. Therefore, traditional dance training can serve as an effective alternative activity for fostering character development, creativity, self-confidence, and cultural preservation within school and community environments.